Drying Quality of Mahoni Wood in Various Incising Densities and Two High Temperature-Drying Schedules - Tomy Listyanto; Fadlul Rahman; Hyana Swargarini (Jurnal Ilmu Kehutanan)
The aims of this research were to investigate the effects of interaction between incising densities and two drying schedules on drying rate and defects as well as to examine the effect of incising densities on static bending characteristics of dried mahogany. Tree mahogany (Swietenia mahogany) trees with the diameter of 300-350 mm were cut and sawn into columns with the dimension of 60 mm ×100 mm × 500 mm. Each column was cut into five parts with the length of 500 mm. A small sample with the dimension of 20 mm × 20 mm × 25 mm were taken in between drying sample to measure moisture content. Five incising densities, which were 0 holes/m2 (unincised), 1000 holes/m2, 2000 holes/m2, 3000 holes/m2 and holes/m2, were applied to the drying sample. Samples were dried with two different drying schedules until the moisture content of 12%. Drying rate, defects, and moisture distribution were measured to evaluate the drying quality. Static bending test was applied to examine the strength properties. The results showed that incising densities of 3000-4000 holes/m2 could significantly improve drying rate and final moisture content distribution. There was no significants defects due to the variation of incising densities and drying schedules. No significant decrease of modulus of elasticity and modulus of rupture among five incising densities was found in this research.